Ciudadanía y nación: políticas de control fronterizo e inmigración (2016)
The legal theory of human rights and fundamental rights requires the need for a global legal system that protects both legal categories without any degree of personalistic distinctions such as citizen and immigrant. Under the global legal order, the union of States represents the disappearance of visible and invisible borders, while nation states are called to disappear. Despite the legal-theoretical construction of the binomial human rights/fundamental rights, which expresses a legal-political delimitation that is alien to national law, border control and closure have persisted in those countries that have emerged as economic powers, leading to the lack of recognition of human rights for those non-citizens who are in the search for the rights that would help them live well. The study proposes then the choice of a particular case under analysis, at the border between Ceuta and Melilla, which will question the claim of universality of human rights. For this purpose, an inductive as well as a deductive and pragmatic methodology will be used to contrast the case of border closures with the current theory of fundamental rights.